Peran K.H Ahmad Dahlan dalam Pembentukan Sekolah Muhammadiyah di Yogyakarta Tahun 1911-1922 - Maya Putri; Wakidi Wakidi; Muhammad Basri (FKIP UNIVERSITAS LAMPUNG, 2017)
The objective of this research was to know the action of K.H Ahmad Dahlan in built Muhammadiyah School at Yogyakarta in Year 1911-1922. The method of this research was historical and data collecting techiques of this reserach were literature and documentation techique. To analyze the data techique. The result of this research were 1. There in action of K.H Ahmad Dahlan in built the institution of Madrasah school. 2. K.H Ahmad Dahlan was changed the purpose of education which in the beginning did not in a written form became a writen form. 3. K.H Ahmad Dahlans curriculum name is ISMUBA that combine with tradisional Islam education and dutch-built gubermant school.Penelitian ini bertujuan untuk mengetahui apa sajakah peran normatif K.H Ahmad Dahlan dalam pembentukan sekolah Muhammadiyah Tahun 1911-1922. Metode yang digunakan adalah metode historis dengan teknik pengumpulan data adalah teknik kepustakaan dan dokumentasi. Teknik analisis data yang digunakan adalah teknik analisis data kualitatif. Hasil yang didapat oleh peneliti yaitu 1. K.H Ahmad Dahlan membentuk lembaga sekolah Madrasah. 2. K.H Ahmad Dahlan mengubah tujuan pendidikan yang semula tidak tertulis menjadi tertulis. 3. Kurikulum K.H Ahmad Dahlan bernama ISMUBA memadukan sistem pendidikan tradisional Islam dan sekolah Guberment bentukan Belanda.Kata Kunci: k.h ahmad dahlan, kurikulum, lembaga